Sinisan ameliorates early-life stress-induced depressive-like behaviors by repairing DRN synaptic damage through CaSR - Yu, Qingying; Li, Huan; Cui, Xulan; Zhou, Liuchang; Xie, Zedan; Wang, Shanshan; Deng, Di; Zhao, Jinlan; Sun, Peng; Shi, Yafei; Zhang, Rong (Frontiers in Pharmacology, 2025)
IndroductionEarly-life stress (ELS) is a well-established risk factor for adolescent depression, yet the underlying neurobiological mechanisms remain incompletely understood. The dorsal raphe nucleus (DRN), a key serotonergic center, demonstrates stress-induced synaptic impairments that may underlie depressive phenotypes. Sinisan (SNS), a classical Chinese herbal formula, shows clinical efficacy against mood disorders, but its effects on adolescent stress-induced DRN synaptic damage are unknown.MethodsUsing a maternal separation plus chronic unpredictable mild stress (MSCUMS) model in adolescent rats, we integrated behavioral tests with various neurobiological analyses. Depressive-like behaviors were evaluated, synaptic ultrastructure in the DRN was examined via electron microscopy, and CaSR expression was measured. The therapeutic effects of SNS and the mechanistic role of CaSR were investigated through pharmacological activation (GdCl3).ResultsMS-CUMS induced: (1) depressive-like behaviors, (2) DRN synaptic ultrastructural damage, and (3) Calcium-sensing receptor (CaSR) downregulation. SNS treatment normalized depression/anxiety behaviors, restored CaSR expression and ameliorated synaptic damage. CaSR activation (GdCl3) reversed these deficits, confirming its mechanistic role.DiscussionThese results demonstrate that CaSR mediates ELS-induced DRN synaptic impairment, and SNS exerts rapid antidepressant effects via CaSR upregulation.